PENGARUH KUALITAS PELAYANAN DAN HARGA TERHADAP KEPUASAN PELANGGAN PADA CV. CAHAYA BONANZA ABADI LAMONGAN - Mohamad Rizal Nur Irawan (STIE Mahardhika, 2020)
Customer satisfaction will be formed if it can meet the customer's basic expectations. Many factors influence customer satisfaction, including service quality and price. The problem that the answer to this research is looking for is the effect of partial, simultaneous and dominant independent variables (service quality and price) on customer satisfaction. Data analysis methods used are validity test, reliability test, classic assumption, multiple regression analysis, multiple correlation test, coefficient of determination, F test, t test. The results of multiple linear regression obtained an equation, (Y = 2.936 + 0.098 X1 + 0.246 X2). The t-test results obtained by t count variable service quality 5.434 price 3.704 greater than t table 1.660 between independent variables partially has a significant influence on customer satisfaction. The results obtained from the F test are: F count (75,966)> F table (3,09) means that variables simultaneously have a significant effect on customer satisfaction. From the regression calculation and t count value can be drawn that the most dominant influence on customer satisfaction is price. From the results of the analysis concluded that the independent variable (service quality and price) has a significant influence on customer satisfaction Cv. Cahaya Bonanza Abadi Lamongan.